2007
DOI: 10.1016/j.pbb.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Dependence-induced increases in ethanol self-administration in mice are blocked by the CRF1 receptor antagonist antalarmin and by CRF1 receptor knockout

Abstract: Models of dependence-induced increases in ethanol self-administration will be critical in increasing our understanding of the processes of addiction and relapse, underlying mechanisms, and potential therapeutics. One system that has received considerable attention recently is the CRF 1 system that may mediate the link between anxiety states and relapse drinking. C57BL/6J mice were trained to lever press for ethanol, were made dependent and then were allowed to self-administer ethanol following a period of abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
141
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 40 publications
13
141
0
Order By: Relevance
“…The first line of evidence is that antagonism of CRF 1 receptors attenuates both yohimbine-induced (present report) and dependence-induced increases in alcohol selfadministration (Chu et al 2007;Funk et al 2007;Gehlert et al 2007;Sabino et al 2006). Both in our study and in the study of Funk et al (2007) antalarmin only partially attenuated the increases in alcohol intake, and in neither study, an orderly dose-response curve was observed.…”
Section: Role Of Crf In Yohimbine-induced Increases In Operant Alcohomentioning
confidence: 53%
“…The first line of evidence is that antagonism of CRF 1 receptors attenuates both yohimbine-induced (present report) and dependence-induced increases in alcohol selfadministration (Chu et al 2007;Funk et al 2007;Gehlert et al 2007;Sabino et al 2006). Both in our study and in the study of Funk et al (2007) antalarmin only partially attenuated the increases in alcohol intake, and in neither study, an orderly dose-response curve was observed.…”
Section: Role Of Crf In Yohimbine-induced Increases In Operant Alcohomentioning
confidence: 53%
“…This result is consistent with the hypothesis that the activation of extra-hypothalamic CRF systems is more involved in alcohol drinking motivated by the negative reinforcing properties of the drug (i.e., dependence-induced drinking), but not drinking motivated by the positive reinforcing effects of the drug (i.e., binge-like alcohol drinking and nondependent alcohol drinking; Koob, 2003). Consistent with this notion, nondependent CRF 1 -receptor knockout mice have been observed to drink more alcohol than wild-type controls (Sillaber et al, 2002), but CRF 1 -receptor knockout mice do not exhibit the dependence-induced increases in alcohol drinking observed in wild-type controls (Chu et al, 2007). It remains to be determined if long-term binge-like drinking in a model such as the one used here is capable of eventually producing the motivational symptoms associated with alcohol dependence.…”
Section: Discussionmentioning
confidence: 85%
“…Chronic treatment with a CRF 1 R antagonist abolishes dependence-induced escalation of drinking in rats chronically exposed to high doses of alcohol (Roberto et al 2010b). Likewise, (1) stressors and alcohol withdrawal increase CRF 1 R expression in limbic brain regions (Aguilar-Valles et al 2005;Sommer et al 2008); (2) rats bred for high alcohol preference show increased anxiety-like behavior and CRF 1 R levels (Ciccocioppo et al 2006); and (3) CRF 1 R knockout mice show decreased anxiety-like behavior (Muller et al 2003) and decreased drinking following withdrawal from chronic highdose alcohol (Chu et al 2007). …”
Section: Crf and Alcohol-related Behaviormentioning
confidence: 99%